Atores sociais em disputa: o conflito em torno dos vazios urbanos industriais na Zona Leste de São Paulo - Brás e Mooca - Gonçalves, Felipe de Oliveira (2020)
The city of São Paulo has undergone several transformations due to the new dynamics imposed by industrial deconcentration and economic globalization. These changes have influence the city's productive base and the way in which urban space is produced. The industrial centers, previously located in urban centers, were progressively moved to regions that could obtain better competitive advantages and, consequently, this movement contributed to the formation of urban voids in the areas that housed the city's industrial activity. Such process can be seen in the East Zone of São Paulo, especially between the neighborhoods contiguous to the central region, like Mooca and Brás, once they have several buildings from the industrial era – such as warehouses, factories and land in condition of underutilization. These spaces are often the target of new uses, as they are of great importance due to their central position. In this way, this territory presents itself as an important field of research, as it materializes conflicts over the reconversion of industrial voids. In a territory marked by industrial migration, social actors that were central to the structuring of space are in decline, while others appear in their place. On the scale of everyday life, the consequences of this process are not limited to disputes over the reactivation of these spaces, they are also disputes over the conceptions of the city that arise during movements of urban transformation